The Implementation of Scientific Approach in Teaching English Based on 2013 Curriculum - Burhanuddin Burhanuddin; Arifin Syamaun; Nira Erdiana (Research in English and Education Journal, 2019)
2013 curriculum applies scientific approach in the formal learning process, and the scientific approach offers more chance for students to get more involved in the learning process. The scientific approach stimulates students to think creatively through some steps, and that draw the writer’s attention to conduct such research regarding the scientific approach to prove if implementation of scientific approach can stimulate student to think creatively as result of learning process. This research focuses on the implementation of scientific approach in the classroom at SMA Lab School Unsyiah. This research gather data from two sources; observation during English class to examine the implementation of the method in the class and conducting interview with English teacher to gain deeper data regarding the implementation of scientific approach. Result of this research showed the implementation scientific approach during learning process still need improvement. That was caused by unequal chance received by students to directly participate in the whole steps of scientific approach. Naturally, the implementation of scientific approach is helpful and should be applied during teaching and learning process in school to stimulate students’ activeness.